Development of experimental sporothrichosis in a murine model with yeast and mycelial forms of Sporothrix schenkii - Nobre, Márcia de Oliveira (2018)
Sporotrichosis is a subcutaneous disease that affects both men and a variety of animals caused by the dimorphic fungus Sporothrix schenckii. The aims of this study were to observe differences in virulence between inocula containing the yeast (Y) or mycelial (M) forms, to compare the reactions induced by the two inocula injected in different anatomical sites, and to verify the possibility of horizontal transmission of the disease by contact between infected and healthy animals. All animals were observed during a period of nine weeks. Mice were inoculated subcutaneously in the paw pads and in the regions of the hip and shoulder joints. Another group of non-inoculated healthy mice was kept in direct contact with mice developing the subcutaneous lesions. Animals of groups Y and M developed lesions due to infections and clinical symptoms very characteristic of sporothrichosis. Lesions were more prominent and with longer duration when occurring in the pads than in any other site of inoculation. Non-inoculated mice remained healthy as it occurred to animals in the control group. The development of typical clinical symptoms for sporothrichosis in all inoculated groups suggests that no difference exists in virulence between the yeast and mycelial forms of the same isolated of S. schenckii. Moreover, the paw pads appear to be the site of choice for the inoculation for experimental sporotrichosis in the murine model. In addition, this study also showed that the contact with sick animals and contaminated materials is insufficient to transmit the infection to immune competent animals with intact skin.